Exploration of Factors Shaping Youth Entrepreneur Development in Nepal - Chalise, Dhan Raj; Timilsena , Jagat; Bhandari, Kalpana (Management Dynamics, 2023)
The study aimed to evaluate the current state of youth entrepreneurship development in Nepal and investigate the relationship between various factors such as education training, entrepreneurial skills, access to finance, unemployment, perceived social norms, entrepreneurial motivation, and innovativeness with youth entrepreneurship development. Utilizing a quantitative research design, data was collected from a sample of 200 individuals actively engaged or aspiring in youth entrepreneurship in Nepal, employing a random sampling technique. Through Five-point Likert scale questionnaire, Descriptive Statistics, Correlation Analysis, Regression Analysis, and Reliability Test were utilized to analyze the data and explore the relationships and extent of impact among the variables. The findings indicate significant positive correlations between all pairs of variables examined, suggesting strong relationships between education training, entrepreneurial skills, access to finance, unemployment, perceived social norms, entrepreneurial motivation, innovativeness, and youth entrepreneurship development. Furthermore, the regression analysis revealed that education training, perceived social norms, and entrepreneurial motivation have statistically significant positive effects on youth entrepreneurship development, with innovativeness showing the strongest positive influence. However, entrepreneurial skills, access to finance, and unemployment did not significantly impact youth entrepreneurship development in Nepal. The study provides valuable insights for policymakers, educators, and stakeholders aiming to enhance the youth entrepreneurship ecosystem in Nepal.